Comparative Utility of Doxorubicin, Cyclophosphamide, and Docetaxel in Breast Cancer Treatment in West Sumatera. - Najmiatul Fitria; Intan Nur Rahmadani; Dita Permatasari; Fitri Handayani (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2024)
The large number of breast cancer cases in Indonesia and the high cost of treatment cause the need for utility analysis. West Sumatra province ranks second with the highest prevalence of breast cancer in Indonesia. This study aimed to determine the quality of life of breast cancer patients at the national referral hospital Dr. M. Djamil, West Sumatra, who underwent chemotherapy. This study used a cross-sectional design from January to April 2024. Data collection was done prospectively by filling out questionnaires at the Chemotherapy Unit. Utility value was obtained from filling out a questionnaire with the EQ-5D-5L instrument. Data were analyzed using the Mann-Whitney and Kruskal-Wallis tests. The data obtained was 47 respondents who received Doxorubicin and Cyclophosphamide chemotherapy regimen (24 respondents) and a Docetaxel chemotherapy regimen (23 respondents), all of whom met the inclusion criteria in this study. The average utility value obtained for the doxorubicin and cyclophosphamide regimes is 0.637, and the average utility value for the docetaxel regimen is 0.704. Age did not affect utility (p>0.05), while recent education, occupation, and patient origin affected utility (p<0.05). Both regimens provided similar perceived quality of life and overall health status as measured by utility and VAS scores, suggesting comparable patient-reported quality of life outcomes between these chemotherapy treatments.